(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article analyzes the feasibility of introducing modern information and computer technologies, multimedia tools, and advanced techniques in the process of mastering a foreign language. The necessity of using innovative technologies in the practice of teaching foreign languages is analyzed.